PROGRAM DESAIN PENULANGAN DINDING PENAHAN TANAH (RETAINING WALL) MENGGUNAKAN PERANGKAT LUNAK VISUAL BASIC .NET 2008 - Star, Anastasia; Bella, Rosmiyati A.; Cornelis, Remigildus (Jurnal Teknik Sipil, 2012)
The retaining wall usually used to resist lateral pressure which is caused by backfill material. The stability of retaining wall is obtained mainly from its weight and the weight of the soil at the toe and the heel of retaining wall. The purpose of this research is make a program to design the semi gravity wall and the cantilever wall by using Visual Basic. NET 2008 program. SC Wall 2011 is a result of this research that using programming language of Visual Basic .NET 2008 that used to calculate the stability and reinforcement of the cantilever and semi gravity wall. Based on the output of SC Wall 2011, it shows that the program can be used to design the cantilever wall and the semi gravity wall, because its calculation is faster than the manual calculation. This program needs approximately 1.5 minutes to solve a simple problems.